From "S" to "O": experimental and theoretical insights into the atmospheric degradation mechanism of dithiophosphinic acids. Issue 66 (4th November 2020) - Wang, Zhipeng; Zhang, Yixiang; Liu, Jingjing; Song, Lianjun; Wang, Xueyu; Yang, Xiuying; Xu, Chao; Li, Jun; Ding, Songdong
Abstract : The oxidation behavior and mechanism of five typical DPAH ligands in the air was systematically studied through experimental and theoretical methods. Abstract : Dithiophosphinic acids (DPAHs, expressed as R1 R2 PSSH) are a type of sulfur-donor ligand that have been vastly applied in hydrometallurgy. In particular, DPAHs have shown great potential in highly efficient trivalent actinide/lanthanide separation, which is one of the most challenging tasks in separation science and is of great importance for the development of an advanced fuel cycle in nuclear industry. However, DPAHs have been found liable to undergo oxidative degradation in the air, leading to significant reduction in the selectivity of actinide/lanthanide separation. In this work, the atmospheric degradation of five representative DPAH ligands was investigated for the first time over a sufficiently long period (180 days). The oxidative degradation process of DPAHs elucidated by ESI-MS, 31 P NMR, and FT-IR analyses is R1 R2 PSSH → R1 R2 PSOH → R1 R2 POOH → R1 R2 POO–OOPR1 R2, R1 R2 PSSH → R1 R2 PSS–SSPR1 R2, and R1 R2 PSSH → R1 R2 PSOH → R1 R2 POS–SOPR1 R2 . Meanwhile, the determination of p K a values through pH titration and oxidation product by PXRD further confirms the S → O transformation in the process of DPAH deterioration. DFT calculations suggest that the hydroxyl radical plays the dominant role in the oxidation process of DPAHs and the order in which the oxidation products formed is closely related to the reaction energy barrier. Moreover, nickel salts of DPAHs have shown much higher chemical stability than DPAHs, which was also elaborated through molecular orbital (MO) and adaptive natural density portioning (AdNDP) analyses. This work unambiguously reveals the atmospheric degradation mechanism of DPAHs through both experimental and theoretical approaches. At the application level, the results not only provide an effective way to preserve DPAHs but could also guide the design of more stable sulfur-donor ligands in the future.